[delta]15N and [delta]13C in the Mondego estuary food web: Seasonal variation in producers and consumers - Baeta, Alexandra (2009)
http://www.sciencedirect.com/science/article/B6V7H-4V1KMR2-1/2/b800195eaff45d3f8489262b01e043d2